(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Media is considered as the fourth pillar of democracy. The media has been emerging tremendously in recent times. Media influences the everyday life of the general public and influences in shaping public opinion. Freedom of the Press is guaranteed as a Fundamental right under Article 19 (1) (a) of the Constitution of India. There are several Statutory laws relating to media in India. A media trial refers to the coverage of a criminal case or an investigation by the media before a particular case has been fully adjudicated by a court of law. In recent times, the media transgresses its limit and provides sensationalized false exaggerated information to the general public even before the delivery of judgment by the Judiciary. The media trial violates the right to privacy and the right to a fair trial guaranteed under the Constitution of India. There is a need to regulate the press and media by strengthening the existing legal framework and guidelines.